Hierarchically Structured, Double‐Periodic Inverse Composite Opals. (31st May 2013) - Retsch, Markus; Jonas, Ulrich
Abstract A versatile colloidal templating strategy to fabricate hierarchically structured inverse opals is investigated. A sequence of infiltration and pyrolysis steps provides access to a range of material combinations such as SiO2, Al2O3, or TiO2. The experimental results also document the feasibility of this method to fabricate porous polymer films with a double periodic pore lattice.